Focal non-invasive deep-brain stimulation with temporal interference for the suppression of epileptic biomarkers - Acerbo, Emma; Jegou, Aude; Luff, Charlotte; Dzialecka, Patrycja; Botzanowski, Boris; Missey, Florian; Ngom, Ibrahima; Lagarde, Stanislas; Bartolomei, Fabrice; Cassara, Antonino; Neufeld, Esra; Jirsa, Viktor; et al. (Frontiers in Neuroscience, 2022)
Introduction: Neurostimulation applied from deep brain stimulation (DBS) electrodes is an effective therapeutic intervention in patients suffering from intractable drug-resistant epilepsy when resective surgery is contraindicated or failed. Inhibitory DBS to suppress seizures and associated epileptogenic biomarkers could be performed with high-frequency stimulation (HFS), typically between 100 –165Hz, to various deep-seated targets such as for instance the Mesio-temporal lobe (MTL) which leads to changes in brain rhythms, specifically in the hippocampus. The most prominent alterations concern high-frequency oscillations (HFOs), namely increase in ripples, a reduction in pathological Fast Ripples (FRs), and a decrease in pathological interictal epileptiform discharges (IEDs). Methods: In the current study, we use Temporal Interference (TI) stimulation to provide a non-invasive DBS (130 Hz) of the MTL, specifically the hippocampus, in both mouse model of epilepsy and scale the method using human cadavers to demonstrate the potential efficacy in human patients. Simulations for both mice and human head were performed to calculate the best coordinates in order to reach the hippocampus. Results: This noninvasive DBS increases physiological ripples, and decreases the number of FRs and IEDs in a mouse model of epilepsy. Similarly, we show the inability of 130 Hz transcranial current stimulation (TCS) to achieve similar results. We therefore further demonstrate the translatability to human subjects via measurements of the TI stimulation vs TCS in human cadavers. Results show the better penetration of TI fields into the human hippocampus as compared with TCS. Significance: These results constitute a first proof of the feasibility and efficiency of TI to stimulate at depth an area without impacting the surrounding tissue. The data tend to show the sufficiently focal character of the induced effects and suggest promising therapeutic applications in epilepsy.